Pocket radar guide key radar facts, equations, and data - Curry, G. Richard (Raleigh, NC SciTech Publishing, 2010)
The book covers the following topics about radar concept; frequency; antennas; transmitters; receivers and signal processor; waveforms; radar cross-section; radar equation; detection and search; measurement and tracking; clutter; atmosphere, rain and ionosphere; decibels (dB), and list of symbols.
Electronic reproduction.
Keywords: Radar; Radar -- Handbooks, manuals, etc; Radar transmitters; Radar -- Antennas; Radar -- Interference; Rain and rainfall; Receivers; Signal processing; Tracking radar; Electronic books